Building trustworthy applications on a Service-Oriented Computing paradigm. (27th July 2007) - Tsai, W.T.
In the past few years, we have witnessed rapid progress in Service-Oriented Computing (SOC) and web services, which represent a paradigm shift from the current mainstream Object-Oriented Computing (OOC) paradigm to the SOC paradigm. This shift is changing the way we specify, design, simulate, evaluate, and use computer software. This special issue is devoted to presenting the latest techniques and developments in this area.